Hepatic resections by means of digitoclasia: outcome in twenty patients. - Antonio Ríos Rodríguez; Nancy Capin Sarria; Lidia Torres Aja (Medisur)
Background: Hepatic surgery currently shows impressive advances. Among the newest techniques we can include digitoclasia, created by Ton That Tung. Objective: To describe the results of hepatic resections in patients operated with digitoclasia. Methods: A descriptive, retrospective study of the outcome of twenty patients operated in the hospital “Dr. Gustavo Aldereguía Lima” in Cienfuegos, carried out in a period of ten years. The following variables were analyzed: Age, sex, disease that determined the intervention, kind of hepatic resection, complications and mortality. Findings: Cavernous haemangioma, hepatocarcinoma, hepatic metastasis of colon cancer and politraumatism were the main causes that led to surgical intervention; right hepatectomy was the most frequent technique. Conclusions: Digitoclasia is a quick and safe procedure, even for wide hepatic resections since, even with some levels of complications and mortality, these do not exceed the figures of studies by other authors.